A TRANSLATION ANALYSIS OF DEIXIS IN THE FALL OF THE IMAM A NOVEL BY NAWAL EL SAADAWI AND ITS INDONESIAN TRANSLATION (PRAGMATIC PERSPECTIVE) - Agustyawati, Khoirul Dwi (2011)
The objectives of this study are (1) to describe the types and the functions of deixis in The Fall of The Imam a novel by Nawal El Saadawi and its Indonesian translation, (2) to describe the equivalence of deixis in The Fall of The Imam a novel by Nawal El Saadawi and its Indonesian translation. The writer analyzes the deixis in The Fall of the Imam a novel by Nawal El Saadawi and its Indonesian translation using by referring to Hurford and Brendan theory of deixis, that is reported speech Based on the data analysis, the writer found the types of deixis in The Fall of The Imam a novel by Nawal El Saadawi and its Indonesian translation. They are person deixis, place deixis, time deixis, discourse deixis and social deixis. The writer found 184 numbers belonging the types of deixis, they are personal deixis, place deixis, time deixis, discourse deixis and social deixis. The writer found from 184 data, there are 100 or 54,34% data belong to equivalent translation although there are strategies of shifting, deletion information and adding information but the message of the SL and TL is not different contextually. And there are 84 or 45,66% belong to non equivalent. So it means that the translation of deixis in The Fall of The Imam a novel by Nawal El Saadawi and its Indonesian Translation is not good translation because there are almost a half of 184 data belong to non equivalent translation.